Ownership Structure and Performance of Quoted Industrial Goods Companies in Nigeria - Orjinta, Hope Ifeoma; Ikeogwu, Sunny Nwachonimuya (Advances in Social Sciences Research Journal, 2025)
This study examines the effects of ownership structure on performance of quoted industrial goods firms in Nigeria. The study relies on secondary data derived from various companies’ financial statements and the Nigerian Exchange fact book to determine and measure the level of ownership holdings of various firms in corporate financial statements, applying an all-inclusive multivariate analysis. Samples of 10 industrial goods firms quoted in Nigeria Exchange Group were used for the period of ten years spanning 2015 to 2024. The study employed ex-post facto and longitudinal research design. The secondary sources of data were collected from annual reports of the selected industrial goods companies and five (5) specific objectives and hypotheses were subjected to some preliminary data tests using descriptive statistics, Pearson correlation analysis and variance Inflation Factor and were tested and analyzed using panel regression analysis. The empirical analysis using a total of 100 company-year observations, shows that foreign ownership has negative but significant effect on performance of quoted industrial goods companies in Nigeria which was statistically significant at 5% level of significance while a positive and significant effect were documented for family ownership at 95% confidence level. Institutional ownership and block ownership were found to have positive but insignificant effect on performance of quoted industrial goods companies in Nigeria. In line with the above findings, this study therefore recommends among others that, family members should be encouraged to have shareholding in their respective businesses as this helps in maintaining high performance of firms in Nigeria industrial goods sector while emphasis on foreign shareholding in the firms should be minimized since it was found to have negative and insignificant effect on performance of industrial goods firms in Nigeria.